Analisis Antropometri terhadap Ruang Kendali Traktor Roda Empat Buatan Jepang ‘K’ dan Eropa ‘N’ - Rhamdani Mardiansyah; Mad Yamin (PERTETA, 2012)
ABSTRACT Four-wheeled tractor is one of the most important agricultural machine tools that used in activity of soil tillage. Most of the four wheeled tractor in Indonesia specially designed not for local operators because the design mostly followed by average size operators from the country that create the tractor, especially in the workstation design. Ergonomics approaching of anthropometry analysis have intended to determine safety and comfort level of operator duringoperation the tractor. Anthropometry analysis includes observation natural range of movements (ROM) from Jetis’s farmers in operation the control device toward workstationof tractor made in Japan ‘K’ and Europe ‘N’.This analysis alsodetermine optimum range of control devices was controlled by the hands or feet operator. The result revealed that a positions of the control device in tractor made in Japan ‘K’ were situated inside the functional reach envelope operator of a 5th, 50th, and 95th percentile male Jetis’s farmers. According to analysis result, the tractor made in Japan ‘K’ is more compatible for Jetis’s farmers than tractor made in Europe ‘N’. Keywords: anthropometry, four wheeled tractor, workstation